THE EVOLUTION OF PUBLIC POLICY TOOLS: FROM TRADITIONAL ADMINISTRATION TO INTERACTIVE GOVERNANCE - Białynicki-Birula, Paweł (Pressing Problems of Public Administration, 2019)
The text discusses the evolution of public policy tools in the context of modern administration, public policy and their development. It presents the relationships between the dominant public management paradigms and appropriate sets of tools enabling effective public action. It aims to identify premises for the emergence and use of interactive policy tools connected with a new governance era. On the grounds of public policy these tools are considered to be an effective method for achieving public goals through indirect manipulating policy processes. The text discusses the model used for the selection of procedural tools developed by M. Howlett. In conclusion Author claims that the use of interactive tools is associated with a number of specific problems and/or costs, hence they cannot be perceived in terms of one best solution. This means that the choice of specific solutions should be dictated by a given public policy context, which determines the practical applicability of a particular style of governance and, consequently, of a specific type of policy tool.